Analisis Pemanfaatan Augmented Reality dalam Pembelajaran Matematika dan Dampaknya Terhadap Literasi Matematis Siswa - Siregar, Yulia Anita; Suryani, Didik Rezki; Madani, Riska; Ahyar, Ahyar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the use of Augmented Reality (AR) in mathematics learning and its impact on students' mathematical literacy. This study uses a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The research sample consisted of 68 eighth-grade students divided into an experimental class using AR media and a control class learning conventionally. The mathematical literacy test instruments were developed based on PISA indicators and have been tested for validity and reliability. The data were analyzed using normality tests, linearity tests, Pearson correlation tests, and simple linear regression. The results of the study show that students' mathematical literacy in the experimental class is in the high category with an average score of 78.42, while the use of AR received positive appreciation with an average score of 82.57. Normality and linearity tests showed that the data were normally distributed and the relationship between variables was linear. The Pearson correlation test resulted in r = 0.684 with a significance of 0.000, indicating a strong relationship between the use of AR and mathematical literacy. The regression results showed a coefficient β of 0.615 with R² of 0.468, which means the use of AR contributes 46.8% to the improvement of students' mathematical literacy. These findings confirm that AR is an effective learning medium for enhancing students' conceptual understanding, reasoning skills, and mathematical literacy. This research provides empirical evidence that AR is feasible to implement in mathematics learning to support the mastery of 21st-century competencies.